Fuchs’ uveitis syndrome in dark-colored eyes: a case report: Poster Presentation - Case Report - Ophthalmologist - RINA WULANDARI; FRISMA SAGARA BRILLIYANTO (Majalah Oftalmologi Indonesia, 2023)
Introduction : The prevalence of Fuchs’ uveitis syndrome (FUS), or Fuchs’ heterochromic iridocyclitis, tends to be higher in light colored-eyes population of developed countries, with iris heterochromia as one of the main features. That classic iris finding does not usually present in dark colored-eyes population like Indonesia, in such manner that FUS is often overlooked. Case Illustration : A 38-year-old male presented with decrease vision of right eye four months before admission. There was minimal anterior chamber reaction, dispersed non-pigmented stellate keratic precipitates (KP), moth-eaten iris, posterior subcapsular (PSC) cataract without posterior synechiae and grade 0.5 of vitreous cells. A diagnosis of FUS was made by presenting signs, then cataract surgery was safely performed, and vision significantly improved without exacerbation. Discussion : FUS is a typically mild unilateral uveitis, with iris heterochromia, cyclitis, and cataract without posterior synechiae as its classic findings. Otherwise, iris heterochromia is probably absent in dark- colored eyes, that iris may appear with nodules and or small diffuse atrophy called moth-eaten appearance. Misdiagnosis is mostly caused by holding that iris heterochromia should always be presented and inflammation should be limited in the anterior segment only. FUS responds poorly to steroid and mistreatment with it causes further complication. In addition, cataract surgery is considered safe in FUS. Conclusion : This case shows the importance of evaluating FUS’ atypical signs. Iris heterochromia is sometimes overvalued, and its absence often leads to misdiagnosis. Steroid treatment is controversial, moreover, cataract surgery is safe in this case.